Tanggung Jawab Guru dan Orang Tua Terhadap Pendidikan Moral Anak Perspektif Abdullah Nashih ‘Ulwan Dalam Kitab Tarbiyah Al-Aulãd Fi Al-Islãm. - Jamal, Nur; Juwarno , Juwarno (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2023)
Child morality is a symbol of greatness for both parents and is an important asset that must be possessed by every youth in order to become the pride of the country. Therefore, every educator who is aware of the moral urgency will always prioritize this. However, along with the shifting times and the influence of westernization which is increasingly unstoppable, the individual character of each child becomes dilapidated and difficult to overcome, both by parents and teachers in their respective institutions.The type of research used in this study is library research, where researchers will collect and collect data from studies of the works of experts who can support and complement and deepen analytical studies using documentary techniques.The results of the study show that: first, the responsibilities of teachers and parents for children's moral education are as follows: 1) Avoiding children from participating in behavior, namely supervising children from imitating other people who can lead children astray. 2) Prevent children from drowning in the pleasures and luxuries of the world. 3) prohibiting children from listening to pornographic music and singing, like nowadays when there are trends on social media such as tiktok etc. 4) forbidding children to style and act like women or vice versa women style or act like men. Second, in general, the responsibilities offered by Abdullah Nashih lwan are still relevant to the current situation and can be applied by educators.